2017
DOI: 10.1111/jam.13470
|View full text |Cite
|
Sign up to set email alerts
|

Delignification and enhanced gas release from soil containing lignocellulose by treatment with bacterial lignin degraders

Abstract: The study demonstrates the feasibility of using an in situ bacterial treatment to enhance gas release and resource recovery from landfill soil containing lignocellulosic waste. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 37 publications
(126 reference statements)
0
57
0
1
Order By: Relevance
“…and Paenibacillus sp. were isolated previously as lignin‐degrading strains from woodland soil and municipal waste soil . Genomic DNA from Ochrobactrum sp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Paenibacillus sp. were isolated previously as lignin‐degrading strains from woodland soil and municipal waste soil . Genomic DNA from Ochrobactrum sp.…”
Section: Methodsmentioning
confidence: 99%
“…Currently only a small number of bacteria with the ability to oxidize lignin have been studied in detail: lignin‐oxidizing enzymes have been characterized in Rhodococcus , Amycolatopsis , Pseudomonas , and Streptomyces ; and transcriptomic studies have been reported in P. putida A514 . We have reported the isolation of soil bacteria with lignin oxidation capability from woodland soil and from municipal waste soil . We have therefore investigated via genome sequencing and protein characterization whether these organisms use similar strategies for lignin oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…29. For detection of released phenolic compounds, samples (20 μL) were mixed with distilled water (100 μL) and Folin-Ciocalteu reagent 29 (FCR) (10 μL), and NaCO 3 (100 μL, 4%) was added after 4 min, then incubated in the dark for 30 min at room temperature. Absorbance was then measured at 750 nm with a HIDEX sense microplate reader.…”
Section: Assays For Combination Of Oxidising Enzymes With Accessory Enzymesmentioning
confidence: 99%
“…Lysinibacillus sphaericus strain A1 is a Gram-positive bacterium from the Firmicutes phylum that was isolated from municipal solid waste (MSW) soil in the United Kingdom (1). This lignin-degrading bacterium strain is particularly interesting since, under microscale anaerobic conditions, it presents enhanced methane release from lignocellulose-containing soil, suggesting the potential for in situ treatment and enhancement of landfill soil gas production (1).…”
Section: Genome Announcementmentioning
confidence: 99%
“…This lignin-degrading bacterium strain is particularly interesting since, under microscale anaerobic conditions, it presents enhanced methane release from lignocellulose-containing soil, suggesting the potential for in situ treatment and enhancement of landfill soil gas production (1). …”
Section: Genome Announcementmentioning
confidence: 99%